The Transmission of Bank Liquidity Shocks: Evidence from House Prices*. (24th January 2018) - Dursun-de Neef, H Özlem
Abstract: This article uses the 2007–09 financial crisis as a negative liquidity shock on banks in the USA and analyzes its transmission to the real economy. The ex ante heterogeneity in the amount of long-term debt that matured during the crisis is used to measure the variation in banks' exposure to the liquidity shock. I find that banks transmitted the liquidity shock to the real economy by reducing their loan supply. The reduction was particularly strong for real estate loans. As a result, house prices declined in the MSAs where these banks have branches. Bank capital plays a significant role in the transmission: under-capitalized banks transmitted the liquidity shock, whereas well-capitalized banks' lending did not show any decline.